Coexistence of FTTC and FTTDp network architectures in different VDSL2 scenarios. Issue 2 (20th May 2014) - Mazzenga, F.; Petracca, M.; Vatalaro, F.; Giuliano, R.; Ciccarella, G.
Abstract: Very high speed Digital Subscriber Line type 2 (VDSL2) systems can achieve significant bit rate values depending on the access network architecture and how far‐end crosstalk (FEXT) interference suppression is implemented. The so‐called vectoring technology recently became an implementation reality. It was introduced to dynamically suppress 'self‐FEXT' in a cable of twisted pairs on both downstream (DS) and upstream (US) signals. In the DS direction, crosstalk pre‐compensation precedes modulation, and in the US cancellation follows demodulation. However, vectoring allows to effectively eliminate crosstalk if lines belong to the same vectored group. When this condition is not satisfied, in general, even very few uncontrolled interferers can cause significant performance degradation. In this paper, we evaluate by simulation the VDSL2 performance in scenarios of coexistence between Fibre‐To‐The‐Cabinet (FTTC) with vectoring and Fibre‐To‐The‐Distribution point (FTTDp) architectures. We consider two different combinations of VDSL2 band plans assigned to the FTTC and FTTDp networks. We analyse VDSL2 performance in both cases of absence of spectrum management and implementation of the Downstream Power Back‐Off (DPBO) technique. We also study the throughput trade‐off between the two VDSL2 systems due to DPBO. Results show that, to protect VDSL2 FTTC systems, DPBO must be configured on VDSL2 FTTDp, whereas the investment required to bring the optical fibre to the distribution point could be justified by the improved performance achievable with the FTTDp architecture, even with the VDSL2 band profiles currently used. The presented coexistence analysis can be useful with reference to the G.fast spectrum allocations currently under definition. © 2014 The Authors. Transactions on Emerging Telecommunications Technologies published by John Wiley & Sons, Ltd. Abstract : In this paper, we evaluate the Very high speed Digital Subscriber Line type 2 (VDSL2) performance in scenarios of coexistence between Fibre–To–The–Cabinet (FTTC) with vectoring and Fibre–To–The–Distribution point (FTTDp) architectures, this latter referred to as 'pre–G.fast' solution. Results show that, to protect VDSL2 FTTC systems, Downstream Power Back Off must be implemented at FTTDp, whereas the investment required to bring the optical fibre to the distribution point could be justified by the improved performance achievable with the FTTDp architecture, even with the VDSL2 band profiles currently used.